STRATEGI PERUMDA TIRTANADI MEDAN DALAM MENSEJAHTERAKAN MASYARAKAT MELALUI SDM YANG EFEKTIF - Sy Haura Munawwarah; Nur Ahmadi BI Rahmani (Musytari : Neraca Manajemen, Akuntansi, dan Ekonomi, 2023)
Perumda Tirtanadi Medan, as a water supply company owned by the regional government in Medan, Indonesia, plays a vital role in ensuring a clean and reliable water supply for local residents. Founded with the aim of serving the community’s water needs, this company is committed to providing efficient and quality services. Qualitative Research uses qualitative methods, namely observations, interviews or document reviews carried out during internships. One of the crucial aspects that makes PERUMDA Tirtanadi an integral part of water management is its responsibility for providing clean water. In the context of PERUMDA Tirtanadi Medan, HR is not only about human resource administration, but also about creating a positive work climate and encouraging collaboration between units. Managing conflict and changing organizational culture may be a challenge, but also an opportunity to increase a company’s competitiveness.